Role of Silent Information Regulator 1 (SIRT1) in Regulating Oxidative Stress and Inflammation - Singh, Vivek; Ubaid, Saba (Inflammation, 2020)
Silent information regulator 1 ( SIRT1 ) is a ubiquitously expressed protein and has an intricate role in the pathology, progression, and treatment of several diseases. SIRT1 is a NAD+-dependent deacetylase and regulates gene expression by histone deacetylation. Deletion of SIRT1 in the liver, pancreas, and brain significantly increases the reactive oxygen species (ROS) and inflammatory response. Literature survey on SIRT1 shows the evidence for its role in preventing oxidative stress and inflammation. Oxidative stress and inflammation are closely related pathophysiological processes and are involved in the pathogenesis of a number of chronic disorders such as fatty liver diseases, diabetes, and neurodegenerative diseases. Both oxidative stress and inflammation alter the expression of several genes such as nuclear factor E2 related factor ( Nrf2 ), nuclear factor E2 related factor 2 ( Nef2 ), nuclear factor kappa B ( NF-kB ), pancreatic and duodenal homeobox factor 1 ( PDX1 ), interleukin-1 ( IL1 ), forkhead box class O ( FOXO ), and tumour necrosis factor alpha ( TNF-α ). By annotating this knowledge, we can conclude that modulating the expression of SIRT1 might prevent the onset of diseases inexorably linked to the liver, pancreas, and brain. Graphical Abstract Role of silent information regulator 1 (SIRT1) in the pancreas, brain, and liver